Analisis Konflik SDA antara Masyarakat dengan Pengusaha Air ( Studi Kasus Konflik SDA Desa Kajar Kabupaten Kudus) - Rendyana Bayu Kurniawan; Edi Santoso; Puji Astuti (Journal of Politic and Government Studies, 2017)
Abstract. Water is a natural resource that is very useful and most potential in human life as well as other living beings so that it can be said that water is the source of life on Earth, where the need for water is increasing from time to time. Water is one of the important aspects in the world of agriculture is considering his position as one of the essential needs for plants especially plants in wetlands. Many agricultural water needs are met through irrigation. Irrigation systems are there in Indonesia comes from the existence of a river basin as well as the sources of water. The quality of the streams and springs that well be crucial. The quantity of irrigation water from any source becomes the deciding the smooth process of farm peasants. But the presence of these water sources become endangered because it utilized by persons who are not liable in exploiting existing water sources.The research method being used was qualitative approach with the techniques of data collection were observation, interview and study of documents. Informants in this Study was the Head Office of PKPLH (Perumahan, Kawasan permukiman dan Lingkungan Hidup) of Kudus Regency, Head office BPSDA (Balai Pengelolaan Sumber Daya Air) of Kudus regency, Member of the Commission C DPRD of Kudus Regency, the head of the village of Kajar, entrepreneurs Water and farmers of Kajar Village.The results showed that water resource conflict began around the year 2000 when entrepreneurs began many drinking water. Factors cause of conflict is a source of water commercialization by employers so that farmers are difficult to get water to irrigate rice fields. Government's efforts for conflict resolution is in compliance with the conflict of theory and in accordance with the theory of conflict resolution efforts through the approach of negotiation, mediation, conciliation, and arbitration. A fourth approach that was undertaken by the Government to deal with the conflict, but to no avail.A recommendation Thar could be made for the Government of Kudus is making a binding regulations regarding the business license of water resources and crack down on employers that stubborn firmly not to do activities of exploitation of water again by doing a sustainable socialization and formulating policies by involving the community in order that the policies formulated according on goals and prosper in society.Key words: Water Resources, Exploitation, Conflict, and Conflict Resolution